Natural immunization against Malaria: causal prophylaxis with antibiotics - Friesen, Johannes; Silvie, Olivier; Putrianti, Elyzana Dewi; Hafalla, Julius C. R.; Matuschewski, Kai; Borrmann, Steffen (Science translational medicine, 2010)
Malaria remains the most prevalent vector-borne infectious disease and has the highest rates of fatality. Current antimalarial drug strategies cure malaria or prevent infections but lack a sustained public health impact because they fail to expedite the acquisition of protective immunity. We show that antibiotic administration during transmission of the parasite Plasmodium berghei results in swift acquisition of long-lived, life cycle-specific protection against reinfection with live sporozoites in mice. Antibiotic treatment specifically inhibits the biogenesis and inheritance of the apicoplast in Plasmodium liver stages, resulting in continued liver-stage maturation but subsequent failure to establish blood-stage infection. Exponential expansion of these attenuated liver-stage merozoites from a single sporozoite induces potent immune protection against malaria. If confirmed in residents of malaria-endemic areas, periodic prophylaxis with safe and affordable antibiotics may offer a powerful shortcut toward a needle-free surrogate malaria immunization strategy.